Virals - Reichs, Kathy (London Young Arrow, 2011)
Tory Brennan is the leader of a band of teenage 'sci-philes' who live on an island off the coast of South Carolina and when the group rescues a dog caged for medical testing, they are exposed to an experimental strain of canine parvovirus that changes their lives forever.
Keywords: South Carolina--Morris Island